The Effect of Aeration on the Composting Process of Distillation Waste from Kaffir Lime Leaves - Kanza, Safira; Rizqiyah, Putri Afiqotur; Nurhadiyanti, Vivi; Cahyani, Chandrawati (Department of Agroindustrial Technology, Faculty of Agricultural Technology UGM, 2025)
The extraction process of kaffir lime (Citrus hystrix) leaves is aimed at obtaining its essential oil. However, the residual waste in the form of distilled kaffir lime leaves has not yet been optimally utilised. This residue holds potential as a composting raw material of compost. This study employed naturally occurring mixed-culture microorganism, assessed compost quality based on C/N ratio, temperature changes, yield, visual appearance, and organoleptic characteristics, providing insights into its potential as a sustainable soil amendment. The composting process was conducted using a bin composting method with a chamber volume of 125 cm³. The primary variable investigated was aeration, with two conditions: aerobic and anaerobic. Composting was carried out for a duration of 8 weeks, after which the yield, C/N ratio, organoleptic, and visual characteristics were assessed. The results indicated that anaerobic composting produced a slightly higher yield. In the eighth week, the yield of anaerobic composting was recorded at 2.1%, whereas aerobic composting yielded 1.8%. Both treatments produced compost with C/N ratios that conformed to the Indonesian National Standard (SNI), measured at 15.86 and 16.42 for aerobic and anaerobic processes, respectively.